2014
DOI: 10.1155/2014/530342
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicines Induce Cell Death: The Molecular and Cellular Mechanisms for Cancer Therapy

Abstract: Chinese medicines have long history in treating cancer. With the growing scientific evidence of biomedical researches and clinical trials in cancer therapy, they are increasingly accepted as a complementary and alternative treatment. One of the mechanisms is to induce cancer cell death. Aim. To comprehensively review the publications concerning cancer cell death induced by Chinese medicines in recent years and provide insights on anticancer drug discovery from Chinese medicines. Materials and Methods. Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 154 publications
(91 reference statements)
0
42
0
Order By: Relevance
“…The success with natural product shikonin, which able to induce multiple cell death mechanisms, supports the notion that natural compounds could bypass specific drug resistance developed by tumor cells using simultaneous activation of multiple death pathways (apoptosis, autophagy, necroptosis), as reviewed elsewhere [20, 29, 42, 45, 65, 96, 108, 111, 158, 337-343]. Thus, a rationalized combination of several cell death inducers that complement each other would maximize their efficacy while minimizing their side effects [20, 29, 42, 45, 65, 96, 108, 111, 158, 337-343]. While in vitro studies showed the strong ability of natural compounds to induce non-apoptotic death of tumor cells, more in vivo investigations needed to strengthen this notion before making a leap to clinical application [339-343].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 57%
“…The success with natural product shikonin, which able to induce multiple cell death mechanisms, supports the notion that natural compounds could bypass specific drug resistance developed by tumor cells using simultaneous activation of multiple death pathways (apoptosis, autophagy, necroptosis), as reviewed elsewhere [20, 29, 42, 45, 65, 96, 108, 111, 158, 337-343]. Thus, a rationalized combination of several cell death inducers that complement each other would maximize their efficacy while minimizing their side effects [20, 29, 42, 45, 65, 96, 108, 111, 158, 337-343]. While in vitro studies showed the strong ability of natural compounds to induce non-apoptotic death of tumor cells, more in vivo investigations needed to strengthen this notion before making a leap to clinical application [339-343].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 57%
“…Biomedical research and cancer treatment clinical trials have provided evidence regarding the use of herbal medicines; therefore, they are increasingly being accepted as a complementary and alternative treatment (1). In addition, natural medicines have been reported to have an important role in human health, particularly certain well-studied plants, including Taxus chinensis (Taxus madia) (2), Radix Sophorae flavescentis (Sophora flavescens) (3), Alkanna tinctoria, Lithospermum erythrorhizon and licorice (Glycyrrhiza L) (4).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of proliferation and promotion of apoptosis remain the standard approach of anticancer therapy. For improved therapeutic effect and higher quality of life, multi-target therapy should be emphasized, and the majority of TCMs including HDW exhibit advantages in this respect (27,28). HDW has been reported to be clinically effective with few side effects (5).…”
Section: Discussionmentioning
confidence: 99%